Economic Dimension of Empowerment: Effects of Commercialization and Feminization of Vegetable Farming on Social Status of women in an Urban Fringe of Western Nepal - Adhikari, Rajendra (Himalayan Journal of Sociology and Anthropology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> With the changing context and time, women are no more viewed as passive bearers of pain only. Now they are perceived as active and powerful actors in the society. Their honest and tireless efforts have been the main ways for empowering them and hence uplifting their social status. In this scenario, this article presents the ways women in Hemja, Kaski have been empowering themselves, fulfilling their daily family needs and making some saving through successful commercial vegetable farming. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1498 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.86-105